Exploring social media sharing: the nature of private information shared by Instagram users - Modrall, Melanie H. (My University, 2019)
This research explores the nature of social media sharing of personally identifiable information on Instagram by conducting a content analysis on a total of ten profiles and five posts per profile, selected randomly. Main themes reflected in data were categorized by three methods of information sharing: profile, captions, and images and videos. Fourteen themes were discovered for sharing in profiles and captions, while fifteen were found for images and videos. Results showed users were most likely to share information in their profile (64.1%) and most commonly shared their gender presentation, face, and location. This correlates with previous research concerning privacy and security risks from social media sharing, indicating that these concepts need to be re-evaluated to remain relevant. Originally written for an upper-level sociology course at MacEwan University, this work appears in an open textbook entitled Navigating an Undergraduate Degree in the Social Sciences: Tips and Strategies as a sample research report in Appendix 2.
Keywords: social media; privacy; information sharing